ASSESSMENT OF DYNAMICS OF INFECTIOUS DISEASE ECOLOGY AND EVALUATION OF HUMAN-MOSQUITO INTERACTIONS IN GWAGWALADA TOWN, FCT-ABUJA. - U.N, GIMBA, (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Gwagwalada-FCT climate is suitable for several mosquito species capable of transmitting pathogens to humans. The objective of this research, as a theoretical framework, is to assess knowledge of mosquito-borne disease in Gwagwalada-Abuja, as well as perceptions and practices of mosquito prevention. Five demographic and socioeconomic variables. Knowledge of mosquito-borne diseases within the area was generally low, with only few individual correctly identifying Malaria as a threat in the area. These results can enhance existing public health programs by increasing knowledge, addressing public uncertainty and addressing ways to make recommended practices more effective with the knowledge of how different aspects are perceived by the varying groups within the community.